Hypervalent hydridosilicate in the Na–Si–H system - Spektor, Kristina; Kohlmann, Holger; Druzhbin, Dmitrii; Crichton, Wilson A.; Bhat, Shrikant; Simak, Sergei I.; Vekilova, Olga Yu; Häussermann, Ulrich (Frontiers in Chemistry, 2023)
Hydrogenation reactions at gigapascal pressures can yield hydrogen-rich materials with properties relating to superconductivity, ion conductivity and hydrogen storage. Here we investigated the ternary Na-Si-H system by computational structure prediction and in situ synchrotron diffraction studies of reaction mixtures NaH-Si-H 2 at 5 -10 GPa. Structure prediction indicated the existence of various hypervalent hydrido silicate phases with compositions Na m SiH (4+m) (m = 1-3) at comparatively low pressures, 0 -20 GPa. These ternary Na-Si-H phases share as a common structural feature octahedral SiH 6 2-complexes which are condensed into chains for m = 1 and occur as isolated species for m = 2, 3. In situ studies demonstrated the formation of the double salt Na 3 [SiH 6 ]H (Na 3 SiH 7 , m = 3) containing both octahedral SiH 6 2-moieties and hydridic H -. Upon formation at elevated temperatures (>500 °C) Na 3 SiH 7 attains a tetragonal structure (P4/mbm, Z = 2) which during cooling transforms to an orthorhombic polymorph (Pbam, Z = 4). Upon decompression Pbam-Na 3 SiH 7 was retained to approx. 4.5 GPa, below which a further transition into a yet unknown polymorph occurred. Na 3 SiH 7 is a new representative of yet elusive hydrido silicates compounds. Its double salt nature and polymorphism is strongly reminiscent of fluorosilicates and -germanates.